The Challenges in Diagnosing Sturge-Weber Syndrome (SWS) with Corneal Disorder - Fika Rahmawati; Ismi Zuhria (Vision Science and Eye Health Journal, 2026)
Introduction: Sturge-Weber syndrome (SWS) or encephalofacial angiomatosis consists of a facial cutaneous vascular malformation (port-wine stain) with ipsilateral leptomeningeal vascular malformation. The characteristic facial port-wine stain involves the eyelid, anterior chamber, cornea, choroid, and retina. Other lesions sometimes seen are cataract, corneal degeneration, uveitis, intraocular haemorrhage, and heterochromia of the iris. Case Presentation: A 54-year-old woman presented with a chief complaint of right-eye glare. The patient cannot really remember when it started. Other complaints include eye pain, blurriness and discomfort. Red eyes were irritatingly denied; history of illness, hemangioma since birth, stroke, hypertension, and diabetes mellitus. The left eye has been blind for 40 years. Visual acuity from the right eye is 5/24 pinhole and 5/7.5 light perception from the left eye. The intraocular pressure (IOP) were normal in both eyes. Tear breakup time and Schirmer test showed dry eye. The segment anterior to the right eye showed a hazy cornea and lens opacity. The specular microscope showed higher coefficient variation. Conclusions: Establishing a diagnosis in SWS patient with corneal disorders is difficult, however, routine evaluation remains necessary to maintain eye health and sharp vision, especially in the last eye.